Pengendalian Persediaan di Distributor Hasil - Kurniawan, Daniel; Palit, Herry Christian (Jurnal Titra, 2013)
Hasil distributor runs a building equipment product. The service of this company is dealing with retailers demand using make to order system. There are some sales difficulties issues in Hasil distributor, therefore in some occasion there will be an unfullfilled demand conditions.Â Based on issues faced by the Hasil distributor, we do the analysis to control inventory. The analysis is using forecasting method, in order to predict retailers demand to Hasil distributor in the future. Forecasting method that are used to support the analysis are time series with moving average method, single ex smoothing, double ex smoothing, and winter method. The calculation of EOQ (Economic Order Quantity) multi item will be based on the forecasting result which will be useful for supply control in Hasil distributor and for minimizing the supply cost.The analysis is using the comparison between company method and EOQ multi item method for period of three months. Company method shows 28% fullfilledÂ demand and 72% unfullfilled demand with lost sale IDR. 14,593,936,- while the result from EOQ multi items is 56% fullfilledÂ demand and 44% unfullfilled demand with holding cost IDR. 56.507,-. Based on the above result, EOQ multi item method gives better result than the company method.